Reflection of the formation of the "Soviet" cultural code in Kazakh family law in visual sources of the 20-30s of the twentieth century - Assymova, Д.Б.; Kalkayeva, Н.Б. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2024)
The article is devoted to the history of Kazakh family law in the 20s and 30s of the twentieth century. To be more specific, we will talk about the impact of the first decisions of the Soviet government on the institution of the family in the transitional period of Kazakh history. The abolition of laws governing family relations in Kazakh society before the arrival of the Bolsheviks. The influence of Soviet laws governing the institution of the family on family members. The family is the catalyst for change in a woman's life. The disappearance of polygamous families. The emancipation of a woman. New phenomena in the life of a woman who has received "freedom". New tasks and services outside the household. Differences in the life of a city dweller and a woman from the village. During the article, the presentation of the above problems by visual sources was analyzed. Based on the visual sources considered during the study, an analysis of the elements of tradition and modernism of the Kazakh family at the indicated time was carried out, the dynamics of changes, the mutual unity of the family, the relationship between members, the gender aspect, the propensity to film family issues, and culture were determined. On the basis of visual data, a step was taken towards defining the Soviet cultural code through a description of the material nature surrounding the family. At the beginning of the 20th century, a step was taken towards determining the representation of the historical and political situation in Kazakhstan and their influence on the concept of the family in visual data. In preparing the article, we tried to show the history of Kazakhstan at the beginning of the 20th century through the history of the family, based on a visual representation of the family, through the essence of family life, the main unit of society. In the process of working with visual data on family history, regional, local research methods were used.